The Needs of Patients with Substance Use Disorder Who Presented at Treatment Centers (AMATEM) - Karakaya, İbrahim and Saçaklı, Gamze and Bilici, Rabia and Ögel, Kültegin (Addicta: The Turkish Journal on Addictions, 2022)
The purpose of this study was to determine the psychological, social, and economic needs of patients who presented at the Alcohol and Substance Addiction Research, Treatment, and Training Centers in Turkey. This study was conducted with patients who presented at the Alcohol and Substance Addiction Research, Treatment, and Training Centers in six provinces (Adana, Konya, Gaziantep, Manisa, Samsun, and Elazığ) between 2017 and 2018. The data were collected using a sociodemographic form and a structured questionnaire to assess the needs of patients. The evaluation was made of 328 participants, comprising 314 males, 9 females, and 5 of unstated gender. Of these, 83.5% were inpatients and 16.5% were outpatients, and 42.1% were using more than one substance, reported as opiates by 30.1% and alcohol by 15.5%. The results of this study showed that the patients who sought treatment for substance addiction were mostly supported by their families and also needed a job they can perform with sufficient income to provide a livelihood. These results also suggested that patients with substance use disorder need rehabilitation programs to be able to develop professional and social skills, allow them to discover their own areas of interest, and develop physical exercise habits.